Are Either or Both Hyperuricemia and Xanthine Oxidase Directly Toxic to the Vasculature? A critical appraisal - Neogi, Tuhina (2012)
Basic research and clinical studies have implicated a role for hyperuricemia and for xanthine oxidoreductase (XOR), the enzyme that generates uric acid (UA), in not only gout but also vascular diseases. At present, asymptomatic hyperuricemia (i.e., in the absence of gout, urate nephrolithiasis, or tumor lysis syndrome) is not an indication for therapy. With the rise over the past several decades in prevalence of both gout and hyperuricemia, clarifying the potential adverse effects of hyperuricemia (in patients with and without gout) is of public health importance. UA is not simply an inert end-product of purine metabolism in humans, but rather has potential antioxidant, pro-oxidant, and pro-inflammatory effects. However controversy remains as to which, if any, of these effects are of clinical relevance in development and complications of human vascular diseases in gout and asymptomatic hyperuricemia. Clearly, not all individuals with hyperuricemia develop gout, and studies to date have also been unable to clarify in which subjects hyperuricemia may have detrimental effects on the vasculature. Further, studies of urate-lowering therapy with XOR inhibition or uricosuric agents have not been able to definitively identify whether any such effects may be mediated by UA versus XO. Adequately sized, prospective randomized clinical trials of sufficient duration, and employing appropriate biomarkers, now appear critical to resolve the putative toxic roles of UA and XO in the human arterial circulation.